Entre as kakxop: uma etnografia da aprendizagem e dos cantos das crianças tikmũ’ũn - Barbara Viggiano Rocha da Silva (2019)
This is an academic work about Tikmũ'ũn childhood (these indigenous peoples are also known as Maxakali), northen of Minas Gerais inhabitants, highlighting the dimensions of their lives most connected to sound production, appreciation and reinvention. It was made mainly through ethnography resulting from fieldwork in dialogue with other ethnographies. I try to approach the relation of the acoustic works produced by the tikmũ'ũn children with an ethnography that also considers the moments when they are not producing sounds considered by the hegemonic tradition as musical. Intending to unveil the meanings and motivations of the tikmũ'ũn children (kakxop) to perform practices and productions in which sound occupies a prominent position I was led to scrutinize their play, their free engagement in household chores, their interactions with the various beings that live among them, their frolicking, their diverse learnings, in which they experience unique movements, sensations, and powers, that may constitute their own form of shamanism. The autonomous participation of kakxop in rituals, parties, healing events, initiation, private intimacy of home or memory of dreams evoke their affections and gradually awaken their own capacities, and are therefore indispensable and made possible by the zeal of the Tikmũ'ũn. The care of adults with kakxop is demonstrated in the careful fabrication of the infant body, both by the familiarization engendered by shared food flows, spaces, activities, and singing, as well as by the adoption of other subjectivities in the experimentation of multiple affections that enable them to dilute humanity itself into more becomings. In their daily practices imbued with playfulness and joy among peers, reaffirmed in ritual moments (that stands out in everyday life, not from everyday life) the kakxop are relating and sharing affections with various subjects and helping to maintain Tikmũ'ũn own ways ofliving.